Editorial In(ter)ference: Errata and Aporia in Lolita - Bruce Stone (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2010)
First identified in 1976, Lolita's calendar problem—the discrepant dates between Humbert's manuscript confession and John Ray's Foreword—remains the most stubborn enigma in the novel. Because the problem hinges on the notion of textual error, and on the reliability of Ray's claim that he has corrected the “obvious solecisms” in Humbert's manuscript, this paper begins by establishing the existence of Lolita's textual errata: a list of thirty-one solecisms appears at the end of the article. While the errata tell us little about the calendar problem, there is additional evidence—woven into the novel's structure and emerging in its connections to “'That in Aleppo Once…'”, Nabokov's 1943 short story—to support the conclusion that Humbert has fabricated much of his confession, and especially its last nine chapters. John Ray's Foreword, then, plays a crucial role in demarcating the boundaries of the “real” in the novel. Still a bumbler and buffoon, Ray does leave a detectable presence in Humbert's manuscript, a finding that serves to rebut the claim that Ray is Humbert's invention and which necessitates an alternate theory of the “real” in the novel's concluding chapters. The theory outlined in this paper begins to reconcile the text's discrepant dates and posits the innocence of Humbert's victim. Ultimately, the novel is engineered to conceal as much as it reveals, to leave readers with errata and aporia, error and uncertainty—fundamental conditions of Nabokov's aesthetic.